Empagliflozin prevents cardiomyopathy via sGC-cGMP-PKG pathway in type 2 diabetes mice. (2nd August 2019) - Xue, Mei; Li, Ting; Wang, Yue; Chang, Yunpeng; Cheng, Ying; Lu, Yunhong; Liu, Xiangyang; Xu, Linxin; Li, Xiaoyu; Yu, Xiaochen; Sun, Bei; Chen, Liming
Abstract: Cardiovascular complications contribute to the major mortality and morbidity in type 2 diabetes. Diabetic cardiomyopathy (DCM) is increasingly recognized as an important cause of heart failure. EMPA-REG OUTCOME trial has reported that empagliflozin, the sodium-glucose cotransporter 2 inhibitor, exerts cardiovascular benefits on diabetic population. However, the mechanism by which empagliflozin alleviates DCM still remains unclear. In the current study, we investigated the cardiac protective effects of empagliflozin on spontaneous type 2 diabetic db/db mice and its potential mechanism. Eight weeks of empagliflozin treatment (10 mg/kg/day) decreased body weight and blood glucose level, and increased urinary glucose excretion (UGE) in diabetic mice. Echocardiography revealed that both systolic and diastolic functions of db/db mice were also obviously improved by empagliflozin. Furthermore, empagliflozin-treated diabetic mice presented with amelioration of cardiac hypertrophy and fibrosis. In addition, diabetic hearts exhibited the deterioration of oxidative stress, apoptosis and pyroptosis, while these effects were significantly counteracted after empagliflozin treatment. Moreover, empagliflozin rescued diabetes-induced suppression of sGC (soluble guanylate cyclase enzyme)-cGMP (cyclic guanosine monophosphate)-PKG (cGMP-dependent protein kinase) pathway. However, when sGC-β expression of hearts was inhibited by transvascular delivery of small interfering RNA, cardiac dysfunction was aggravated and the advantages of empagliflozin were reversed through inhibiting sGC-cGMP-PKG pathway. Collectively, these findings indicate that empagliflozin improves cardiac function involving the inhibition of oxidative stress-induced injury via sGC-cGMP-PKG pathway and may be a promising therapeutic option for DCM.